Monitoring of annual effective dose (AED) in surface soils of Ahero rice fields, Kenya - Mukanda Kere Wanyama; Michael Nakitare Waswa; Linda Ouma (ITEGAM-JETIA, 2023)
The annual effective doses (AED) both AED (in) and AED (out) in the surface soils of Ahero rice fields, Kenya were investigated. The associated health risk of the soils from the four fields Field 1, Field 2, Field 3 and Field 4 was measured using gamma ray spectrometric technique employing Sodium Iodide Thallium doped detector. Five surface soil samples were collected at a depth of 15 – 20 cm from the Field 1, Field 2, Field 3 and two samples from Field 4. The average AED (in) of 0.30  mSv/y and an average AED (out) of 0.2  mSv/y for field 1, an average AED (in) of 0.19  mSv/y, an average AED (out) of 0.20 mSv/y for field 2, an average AED (in) of 0.28  mSv/y and an average AED (out) of 0.18 mSv/y for field 3 and an average AED (in) of 0.34  mSv/y and an average AED (out) of 0.2  mSv/y for field 4. All the AED values both in and out from the four fields were below the recommended level of 1mSv/y. The values indicate that there is no health hazard associated with the surface soils of the study area to the farmers and the general population.